Dissociating Sensory and Motor Components of Inhibition of Return - Anne B. Sereno; Cameron B. Jeter; Vani Pariyadath; Kevin A. Briand (The Scientific World Journal)
Two explanations for inhibition of return (IOR) have been proposed. The first is that IOR reflects inhibition of attentional processing at previously cued locations, resulting in altered sensory analysis. The second is that IOR reflects the inhibition of responses directed towards those previously cued locations. We used a variant of a double-saccade paradigm to dissociate these two proposed effects of IOR and attempted to reveal both effects within the context of a single experimental task. Subjects viewed a series of exogenous cues and then made a localization response to subsequent targets with either a target-directed saccade or a pointing response. Results were similar for both response modes. An important finding was that the pattern of IOR depended critically on how subjects reacted to the exogenous cues. Subjects either oriented to the cued locations (via saccades or pointing) prior to responding to the target (Respond), or passively viewed the cues before responding (Ignore). In the Respond condition, IOR was observed at the most recently cued position. Although this could be consistent with an altered sensory interpretation, it would also be consistent with a spatiotopic representation. In the Ignore condition, the sole inhibited location was not the most recently cued position, but the first cued position. This finding is surprising and in conflict with previous work with multiple exogenous cues. The data are discussed in relation to a number of prominent issues in the area of IOR and suggest important new constraints and boundary conditions.